Excitement TEM-horn antenna by impulsive relativistic electron beam - Balakirev, V.A.; Gaponenko, N.I.; Gorban, A.M.; Gorozhanin, D.V.; Egorov, A.M.; Ermolenko, V.V.; Lonin, Yu.F.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2000)
In the given operation the opportunity of reception powerful electromagnetic irradiation (EMI) is observationally explored by excitation by a impulsive relativistic electronic beam (IREB) of a TEM-horn antenna. It is revealed, that at such expedient of excitation of the TEM-horn antenna, the signal of radiation of the antenna contains three various components caused by oscillation of radiation by forward front IREB, high-voltage discharge between plates irradiation of TEM-horn antenna a and resonant properties of the antenna device.